Migration of chlorinated compounds on products quality and dioxins releasing during pyrolysis of oily sludge with high chlorine content. (15th December 2021) - Lin, Fawei; Xiang, Li; Sun, Bingyan; Li, Jiantao; Yan, Beibei; He, Xiaopeng; Liu, Gang; Chen, Guanyi
Graphical abstract: Highlights: The migration of CPs during pyrolysis of OS with different CCs are fully analyzed. CH2 Cl2 and C6 H4 Cl2 are dominant in 12 kinds of detected OCPs in pyrolytic products. The interaction between OS and PVC promotes carbonization and polymerization. Pyrolysis effectively prevents formation of PCDD/Fs, especially for PCDFs. Abstract: Oily sludge (OS) is recognized as the hazardous waste and presence of Cl containing compounds causes severe potential environmental risks. This paper systematically analyzed the distribution of Cl-containing pollutants (CPs) in oil and gas that are ignored previously but have high toxicity. Three model additives, NaCl, PVC, and DCB, were selected to represent inorganic chlorine salt, organic polymers, and Cl-hydrocarbons, respectively. NaCl could retain 99 % of total Cl in the solid residue while PVC released more proportional Cl into gas, ca. 33%. A variety of organic CPs were detected in pyrolytic oil and gas with CH2 Cl2 and C6 H4 Cl2 dominant. The synergy between OS and PVC strengthened with more PVC addition, which promoted carbonization and polymerization to generate more carbon matrix in solid residue. Pyrolysis effectively prevented formation of PCDFs compared with combustion thus exhibiting superiority on inhibiting formation of dioxins. Future work should devote to solve the environmental risks from CPs in pyrolytic products with the strategies including stabilization of Cl in solid residue and cracking of Cl-macromolecules into HCl.